QUANTUM DOTS AND MAGNETIC NANOPARTICLES FOR EARLY DISEASE DETECTION (Journal of Medical & Health Sciences Review, 2025)
In order to improve treatment outcomes and lower healthcare costs, early disease detection is essential. However, traditional diagnostic techniques frequently lack the sensitivity, speed, and multiplexing capabilities needed for prompt intervention. By creating a hybrid nanodiagnostic platform that combines the magnetic capabilities of superparamagnetic iron oxide nanoparticles (SPIONs) with the fluorescent qualities of quantum dots (QDs), this work overcomes these constraints. To target clinically significant protein and nucleic acid biomarkers, such as prostate-specific antigen (PSA), alpha-fetoprotein (AFP), HER2/neu, KRAS mutations, and miRNA-21, cadmium selenide/zinc sulfide (CdSe/ZnS) QDs and functionalized SPIONs were created and conjugated.By combining magnetic prosperity and fluorescence-based quantification, the platform allowed dual-mode detection, resulting in remarkably high sensitivity, with detection limits as low as 5 pM for proteins and 10 copies per reaction for nucleic acids. High specificity, low nonspecific binding, and effective biomarker localization were shown during validation using ex vivo human tissue samples and in vitro cell lines (MCF-7, HeLa, HepG2, LNCaP). Superior performance over conventional techniques such as PCR and ELISA was found through comparative analysis; these techniques offered improved signal-to-noise ratios, multiplexing capabilities, and faster results (less than two hours). TEM, HR-TEM, UV-Vis, FTIR, and XRD characterization methods confirmed the nanoparticles' successful functionalization, structural integrity, and crystallinity. The platform's potential as a flexible, quick, and sensitive diagnostic tool for early disease detection is highlighted in this study, opening the door for enhanced clinical results.